How Far Takaful Efficiency Has Been Researched? : A Bibliometric Approach from Dimensions Database - Mia Sari; Siti Maysyaroh (Islamic Marketing Review, 2022)
This study utilizes a bibliometric approach to investigate efficiency in the takaful industry, which has been under-researched in the literature. Focusing on the theme of "Takaful Efficiency," this study is the first of its kind in this field. The aim is to analyze the development and contribution of research on takaful efficiency in the literature. Data was retrieved from the Dimension.ai platform, and a total of 71 documents were used, with the majority being scientific articles. The analysis shows that scientific articles are the most widely used publication type in this study. Through the mapping of journals and research, it can be seen that the discussion on takaful efficiency is still active and fluctuates every year. In recent years, competition in the insurance sector, especially takaful, has increased, and research indicates a positive relationship between competition and cost efficiency in the takaful industry. Interestingly, this study provides a research path from the results obtained based on seven clusters. These findings can provide valuable guidance for future studies, takaful industry practitioners, as well as policy makers in developing more effective and informed strategies. In addition, this study also contributes to the development of knowledge by illustrating research trends and factors that contribute to efficiency in the context of the takaful industry.